2020
DOI: 10.1364/optica.377886
|View full text |Cite
|
Sign up to set email alerts
|

Strain tuning of the emission axis of quantum emitters in an atomically thin semiconductor

Abstract: Strain engineering is a natural route to control the electronic and optical properties of two-dimensional (2D) materials. Recently, 2D semiconductors have also been demonstrated as an intriguing host of strain-induced quantum-confined emitters with unique valley properties inherited from the host semiconductor. Here, we study the continuous and reversible tuning of the light emitted by such localized emitters in a monolayer tungsten diselenide embedded in a van der Waals hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…It has been shown that nanopillars with equal diameter are associated with a random number of emitters per site and that these emitters can have widely distributed emission energies over 100 meV, even for very small structures of 100 nm size. 16,20 Tuning of emission energy has been demonstrated through applying an out-of-plane electric field 27 or in-plane strain, 28,29 but the tuning range of 2−20 meV is much smaller than the inhomogeneous distribution of the emission energy. Also, the local in-plane strain applied to WSe 2 structures has only been simulated rather than experimentally measured.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that nanopillars with equal diameter are associated with a random number of emitters per site and that these emitters can have widely distributed emission energies over 100 meV, even for very small structures of 100 nm size. 16,20 Tuning of emission energy has been demonstrated through applying an out-of-plane electric field 27 or in-plane strain, 28,29 but the tuning range of 2−20 meV is much smaller than the inhomogeneous distribution of the emission energy. Also, the local in-plane strain applied to WSe 2 structures has only been simulated rather than experimentally measured.…”
mentioning
confidence: 99%
“…Also, the local in-plane strain applied to WSe 2 structures has only been simulated rather than experimentally measured. 28,29 On the other hand, there have been experimental and theoretical efforts to attribute emitter creation in these systems to the intrinsic defect-state 30 or the combination of strain and intrinsic defects. 31 In this work, we elucidate the role of strain by a careful study of the emission energy of bright localized emitters hosted by atomically thin WSe 2 , along with its relationship to the local strain induced by mirco-structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a nanocube cavity array was exploited to induce strain and drive more efficient X L emission through Purcell enhancement [14], yet without the ability to control their radiative emission properties. As further practical applications, experiments inducing X L with nano-structures and controlling its frequency through actuators were reported [15,16]. However, these studies have only been performed at cryogenic temperatures because of the small exciton binding energy of X L [17], which leads to a much lower quantum yield at room temperature compared to the overwhelming radiative emission of neutral exciton (X 0 ) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…8 These systems have, so far, demonstrated promising properties including quantum emission up to room temperature, 8,17,18 electrostatic control of spin-valley-photon interfaces in TMDCs, [19][20][21] and coherence times up to microseconds. 22,23 The possibility of deterministic positioning 24,25 and control 26 of optically active emitters via strain engineering has also been demonstrated. Importantly, 2D material platforms also offer the opportunity to image 27 and controllably fabricate quantum defects at atomically precise locations using present day scanning probe technologies like aberration corrected transmission electron microscopy and low tem-perature scanning tunnelling microscopy.…”
mentioning
confidence: 99%